Nurses’ characteristics on health believes and adaptive health behaviors of hypertension elders in urban communities Bangkok - จิรธรรมคุณ, เสาวลักษณ์; คุ้มทวีพร, พัสมณฑ์ (Journal of Nursing, Siam University, 2019)
This qualitative study was based on grounded theory method. This study aimed to examine nurses’ characteristics inducing health believes and adaptive health behaviors of hypertension elders within Thai urban communities. The population were the in controlled hypertension elders. The forty-four participants were selected by inclusion criteria and were tested before participating the focus groups that no dementia or depression. Seven focus groups were conducted with the permission of the samples. Participants’ group discussions were recorded and transcribed. The grounded theory method was used to develop a semi- structured interview guide corresponding to Bertalanfly’s general system model. At the 8th focus group, the interview guide was used to confirm trustworthy of nurses’ characteristics reinforce elders health believes and adaptive health management. Nurses’ characteristics induced elder health believes and adaptive health behaviors that the samples announced as inputs were 1) consideration: nurse characteristics such as sensitive, active listening, positive thinking, trust and communication skills. 2) knowledge: on disease and humanity, and 3) expert: on decision making, coordinating, and monitoring. Process included relationship making, learning promoting, understanding, fact induced perception generating, concept generating, positive thinking, enthusiasm, self-confidence promoting, and living wisdom implementing by nurses. The outputs of sample health believes and adaptive health management were controllable level of blood pressure, steady capable to control blood pressure, and self-confide continually in health management.